Acute Stress Eliminates Female Advantage in Detection of Ambiguous Negative Affect - Daniel J. DeDora; Joshua M. Carlson; Lilianne R. Mujica-Parodi (Evolutionary Psychology, 2011)
The human stress response evolved to maximize an individual's probability of survival when threatened. The present study addressed whether physical danger modulates perception of an unrelated ambiguous threat and, if so, to what extent this response is sex-specific. The authors utilized a first-time tandem skydive as a stressor, which had been previously validated as producing a highly-controlled, genuinely stressful environment. In a counter-balanced within-subjects design, participants wore a virtual reality helmet to complete an emotion-identification task during the plane's ascent (stress condition) and in the laboratory (control condition). Participants were presented static male faces morphed between 20–80% aggression, which gradually emerged from degraded images. Using a binary forced-choice design, participants identified each ambiguous face as aggressive or neutral. Results showed that participants characterized emotion more rapidly under stress versus control conditions. Unexpectedly, the results also show that while women were more sensitive to affect ambiguity than men under control conditions, they exhibited a marked decrease in sensitivity equivalent to men while under stress.